The concept of culture in the context of psychotherapy - Cvetkovic, Anica (2020)
Demographic changes have led to increased interactions between people with diverse cultural backgrounds. Accordingly, the need for culturally sensitive mental health services has increased. The current literature review discusses theoretical and empirical publications issued in the last decade with the aim to explore how culture and cultural skills are approached in the field of psychotherapy. The context of psychotherapy comes with a set of roles, vulnerabilities, and responsibilities. Analyzing how culture is brought into existence in this context can be of great value for the research on mental health. The analyzed literature suggests that the traditional views of culture are prevailing in this area of science. It is identified that a significant number of publications uncritically relies on the social constructs such as the dichotomy “the West” versus “non-West”. These categories are often used to explain the differences among patients in a therapy room. Moreover, a lot of generalizations are made about certain cultures and these are transformed into advice on how to behave with the members of these cultural groups. Addressing the existing gaps in the literature is an essential step for making improvements in the field. This Master’s thesis provides an understanding of the current state of knowledge and it provides suggestions for future research.